Antibiotic versus nonantibiotic products for the treatment of Papillomatous Digital Dermatitis (hairy heel wart) in dairy cattle - Sargeant, J.M.; Gnad, D.P.; Isch, J.; Bathina, H.; Lising, J.; Shirley, John E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A field trial was conducted to compare oxytetracycline to three nonantibiotic therapies using bandage protocols for the treatment of hairy heel warts. Affected feet were bandaged for 4 days with either of the four products. Over a 28-day period following bandage removal, heel warts on 44 cows (11 per treatment group) were evaluated based on size, degree of pain, color, and lesion appearance. No differences were detected among treatments, suggesting that nonantibiotic therapies used in bandage protocols may be as effective as oxytetracycline.
Keywords: Dairy; Hairy heel warts; Therapy; Nonantibiotic